Struktur dan Fungsi Kepemimpinan GKPI Pagar Beringin - Kusnanto Tri Anggoro Nainggolan; Riska Nadeak; Ibelala Gea (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Leadership (leadearship) is a process of influence between individuals or between people in a particular situation, through directed communication activities to achieve a certain goal. Effective leadership will only be realized if an organization is run according to its structure and function. The purpose of this research study is to answer; Definition of leadership? What is the structure and function of leadership at GKPI Pagar Banyan? Is the leadership structure and function at GKPI running well? This study used a qualitative method with a library research approach and interviews.